Role of triple assessment modalities in diagnosis of palpable breast lump - Gadhvi, Ashwinkumar S.; Gadhvi, Udit I.; Bhimani, Dhaval A.; Rajgor, Darshil K. (International Journal of Research in Medical Sciences, 2018)
Background: One fourth of women suffer from breast disease in their lifetime. Carcinoma of breast is the second most common cancer in the world. Timely and accurate diagnosis of breast lump with early intervention can be life saving. There are various modalities for the diagnosis of breast lump such as USG, FNAC and Mammography, MRI etc. but none of them is perfect. There are numerous reports suggesting that if the results of clinical assessment, mammography and FNAC are all combined, the diagnostic accuracy is nearly 100%. Furthermore, these techniques also provide information about tumor size, number, extent and grade preoperatively. Methods: Study was randomized, prospective, observational and longitudinal including 100 patients, selected according to inclusion criteria. Results: The sensitivity, specificity and accuracy of triple test in present study were 98.68%, 87.5%, and 96% respectively. Out of 100, 76 patients were confirmed as having benign lesion and 24 patients having malignant lesion by histopathology examination. Conclusions: Results of triple assessment are same as the results by histopathology examination in majority of cases. It is highly accurate, can be used as a confirmatory diagnostic tool for breast lump, thus there is no need to perform diagnostic open biopsy for breast lump.